Improvisação em dança na educação básica: uma experiência pedagógica com estudantes do ensino fundamental (1º ao 5º ano) - Bueno, Rafael Gouveia (2020)
Dance may afford a wide range of apprenticeship in the school environment. The students, through this language, when exploring the ludic aspect of pedagogical activities get in touch with experiences that instigate and allow the improvement of their creativity in order to achieve movement freedom, expression and the development of other dimensions of body´s subjectivities. The present text intents to reflect upon the experience developed during dance classes based on contemporary pedagogical approaches with students from 1st up to 5th grades of elementary school at Escola Municipal de Tempo Integral Dona Venância Magalhães Cotrim, from Rede Municipal de Ensino de Itumbiara (Goiás). On this process, theorical-methodological articulations are woven with authors that are thinking the presence of dance in the school, especially those who believe in improvisation as a creative and pedagogical resource. As an artist-teaching, I traverse and I am traversed by singular experiences that corroborate for knowledge production in classroom ground, in the inner space of basic education. At last, a pedagogical experience embraced by a sensitive and significant regard which is in contact with challenges and possibilities of thinking dance and artistic creation in the educational context is elucidate.